Dietary and physical activity strategies to prevent type 2 diabetes in South Asian adults: protocol for a systematic review. Issue 6 (2nd July 2017) - Muilwijk, Mirthe; Stronks, Karien; Qureshi, Samera Azeem; Beune, Erik; Celis-Morales, Carlos; Gill, Jason; Sheikh, Aziz; Jenum, Anne Karen; van Valkengoed, Irene GM
Abstract : Introduction: Type 2 diabetes (T2D) is a major health concern among populations of South Asian ethnicity. Although dietary and physical activity interventions may reduce the risk of T2D, the effectiveness has been moderate among South Asians. This might (in part) be because this subgroup follows strategies that were originally developed for interventions among other populations. Therefore, this review aims to assess the evidence for the current dietary and physical activity strategies recommended in T2D prevention intervention studies and guidelines for South Asians. Methods and analysis: Included will be all studies and guidelines on dietary and/or physical activity strategies to prevent T2D in adult South Asians. Two reviewers will search online databases from their start until the present date for published and unpublished experimental/quasiexperimental studies, with at least an abstract in English. References of identified articles and key reviews will be screened for additional studies. Guidelines will be identified by searches in online databases and websites of public organisations. Finally, expert consultations will be held to supplement any missing information. Trial quality will be assessed with the Quality Assessment Tool for Quantitative Studies Data, and guidelines with the Appraisal of Guidelines for Research & Evaluation II. Data on the strategies recommended, targeting and evidence on effectiveness will be extracted by two reviewers and presented in tabular and narrative forms. Recommendations will be compared with the National Institute for Health and Care Excellence guidelines [PH35]. Overall findings on dietary and physical activity recommendations, as well as findings for specific subgroups (eg, by sex), will be discussed. Ethics and dissemination: Ethics assessment is not required. Start date: 1 January 2016, finishing and reporting date 31 July 2016. Results will be published in a peer-reviewed scientific journal, the project report of EuroDHYAN (www.eurodhyan.eu) and in a PhD dissertation. Trial registration number: The protocol is registered with the International Prospective Register of Systematic Reviews (PROSPERO) registration number CRD42015027067.